Interference of anti-allotype antisera with antigen-antibody binding. - Acuto, O; Manzo, C; Pane, A; Fontana, S; Zappacosta, S; Tosi, R (1975)
Rabbit anti-b4 antisera are capable of inhibiting the antigen-binding ability of antibodies carrying b4 allotype. The data support the hypothesis of the localization of at least one b group allotypic determinant in the V region.